Dewetting dynamics of stressed viscoelastic thin polymer films - Ziebert, Falko; Raphaël, Elie (Physical review. E, Statistical, nonlinear, and soft matter physics, 2009)
Ultrathin polymer films that are produced, e.g., by spin coating are believed to be stressed since polymers are “frozen in” into out-of-equilibrium configurations during this process. In the framework of a viscoelastic thin-film model, we study the effects of lateral residual stresses on the dewetting dynamics of the film. The temporal evolution of the height profiles and the velocity profiles inside the film as well as the dissipation mechanisms are investigated in detail. Both the shape of the profiles and the importance of frictional dissipation vs viscous dissipation inside the film are found to change in the course of dewetting. The interplay of the nonstationary profiles, the relaxing initial stress, and the changes in the dominance of the two dissipation mechanisms caused by nonlinear friction with the substrate is responsible for the rich behavior of the system. In particular, our analysis sheds a different light on the occurrence of the unexpected maximum in the rim width obtained recently in experiments on polystyrene-polydimethylsiloxane systems.
Gesehen am 23.09.2022